Pemanfaatan Kotoran Hewan Sebagai Pupuk Kompos Untuk Tanaman Obat dan Sayur-Sayuran - Malahayati Malahayati; Rezqi Malia; Safrika Safrika; Khaleed Alhamzi; Tri Sutrisno; Farhan Abad; M. Yoga Agustiranda; Baqiatush Shalihat; Salma Auliannisa; Taria Adila; Catur Putri Khairun Nisa (BADAN PENERBIT STIEPARI PRESS, 2024)
One of the places in the Kuta Baro sub-district, Aceh Besar Regency, Aceh Province, is Lambunot Paya Village. Due to Lambunot Paya village's location in a rice field settlement, the majority of the population makes their living as farmers. The surrounding community does not give enough attention to a number of issues, including the problem of freed cattle, which results in an abundance of animal waste in the area, according to the THEMATIC Community Service Lecture (KPM) of the Faculty of Science and Technology (FST) UIN Ar-Raniry, which was held for 40 days in Lambunot Paya Village. During the work program implementation phase, students complete a number of agreed-upon work programs based on their respective scientific disciplines. One such program involves teaching the residents of Lambunot Paya Village science through hands-on compost fertilizer production. The pupils' next work program involves utilizing processed fertilizer to sow vegetables and toga plants.